Pengaruh Servant Leadership, Empowerment dan Komitmen Organisasi Terhadap Organizational Citizenship Behavior Pada Karyawan Royal Hotel n'Lounge Jember: (The Impact of Servant Leadership, Empowerment and Organization Commitments on Organizational Citizenship Behavior (OCB)of Employees Royal Hotel n’Lounge Jember) - Retmita Tata Elsa Manora; Purnamie Titisari; Mochammad Syaharudin (e-Journal Ekonomi Bisnis dan Akuntansi, 2021)
Organizational citizenship behavior is an individual contribution that exceeds the demands of the role at work. Many factors can affect organizational citizenship behavior, namely servant leadership, empowerment and organizational commitment. The population in this study were all employees at the Royal Hotel n'Lounge Jember. The sample in this study as many as 45 respondents using the method used is a census technique in which the entire population is taken as a sample. The analytical method used is multiple linear regression analysis. The results of this study indicate that the significant value of servant leadership is 0.003, the significant empowerment variable is 0.009 and the organizational commitment variable is 0.018 less than the significance value of 0.05. the conclusion obtained in this study is that servant leadership, empowerment and organizational commitment affect organizational citizenship behavior. Company leaders are advised to improve the style of leadership that serves, the company gives responsibility and autonomy to employees and employees of the company are expected to maintain commitment to the organization.